1 A Rare Case of Fryns Syndrome With Concurrent Semilobar Holoprosencephaly. (11th January 2018) - Murray, Glenn; Sago, William
Abstract: Introduction: Fryns syndrome most frequently presents with congenital diaphragmatic hernia and resulting pulmonary hypoplasia. Distal extremity, facial, central nervous system, and cardiovascular malformations have all been documented. Recent studies suggest that Fryns syndrome occurs in 1.3% to 10% of all cases of congenital diaphragmatic hernia (CDH). We present an exceptionally rare case of Fryns syndrome with concurrent semilobar holoprosencephaly. Case Study: A 39-week, 2650 g infant was born to a 32-year-old G6P3 mother. APGAR scores at 1, 5, 10, and 15 minutes were 1, 2, 4, and 4 respectively. At autopsy, a left-sided CDH with resultant left-lung hypoplasia (lung/body weight ratio 0.006) was confirmed. Complete agenesis of the corpus callosum, cerebellar vermis, septum pellucidum, and olfactory bulbs was suggestive of semilobar holoprosencephaly. Polymicrogyria and 80 mL of clear cerebral spinal fluid was present. Head circumference was greater than the 95th percentile for gestational age. A dysmorphic facies was significant for triangular face with broad forehead, low-set ears, atretic external auditory canals, flat nasal bridge and micrognathia. Cord blood and amniocentesis single nucleotide polymorphism whole genome array studies were negative for genetic anomalies. Discussion: Fryns syndrome is a clinically heterogeneous syndrome that has evolved as a diagnostic entity. Lin et al split findings into three different groups. Group 1 patients had 4 of the 6 features defined by Fryns et al. Group 2 had 3 of the 6 features, and group 3 had features that were consistent with Fryns syndrome, but exceeded the current diagnostic spectrum. The 6 core findings are CDH, characteristic facies, characteristic anomalies (polyhydramnios, cloudy cornea, microphthalmia, orofacial cleft, brain malformation, cardiovascular malformation, renal dysplasia, and gastrointestinal and genitourinary malformations), affected siblings, and distal extremity/pulmonary hypoplasia. Despite no known associated cause or gene, Fryns syndrome appears to be inherited in an autosomal recessive pattern. Affected families should be counseled.